BELL’S PALSY ASSOCIATED WITH COVID-19: A CASE REPORT - Anthonius Kurniadi; Leopold Pondaag (Neurologi Manado, 2021)
Introduction. Peripheral neuropathy caused by SARS-CoV-2 infection has been reported. Case reports have described facial nerve palsy associated with Covid-19. Here we report a Bell’s palsy case in a post Covid-19 patient.Case Report. A 43-year-old male came to neurology outpatient clinic complaining of left face palsy since a day before. He has been tested positive for SARS-CoV-2 20 days ago, experienced a mild symptomatic phase, and has been declared negative after the second test 4 days ago. One day before the left facial palsy, he experienced pain on his left ear. Acyclovir, prednisolone, methylcobalamine, and physiotherapy have been given as the treatment of Bell’s palsy after Covid-19 for the patient and came out with good result. After two weeks of treatment, the patient has gained back the muscle strength of his left face to nearly normal condition. Discussion. The SARS-CoV-2 route of entry to the nervous system is still unclear. Peripheral neuropathy is thought to be caused by immunological reaction induced by the virus. The SARS-CoV-2 has caused systemic hyperinflammation with macrophage activation syndrome and cytokine storm. The immune mediated peripheral nerve manifestation occurs characteristically after the acute phase of infection has ended, just like the one experienced by the patient. The treatment was given empirically. Steroids and antiviral have been justly given according to common treatment of Bell’s palsy and showed good results. Analysis of cerebrospinal fluid, blink reflex study, magnetic resonance imaging, and high resolution ultrasonography are advisable ancillary examinations.